1986
DOI: 10.1007/bf00446368
|View full text |Cite
|
Sign up to set email alerts
|

The dual location of ?-oxidation enzymes in germinating pea cotyledons

Abstract: β-Oxidation enzymes were detected both in the mitochondria and microbodies of pea cotyledons. Intact mitochondria did not show β-oxidation enzyme activity but in ruptured mitochondria this activity was high. It is apparent that the mitochondrial membrane barrier prevents rapid access of acyl-CoA substrates to matrix β-oxidation sites. Removal of the membrane barrier permits rapid access of acyl-CoAs and these enzyme activities may then be measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 15 publications
3
16
0
Order By: Relevance
“…This result is in marked contrast to reports from other workers on the localization of the $-oxidation enzymes in higher plant cells (6,12,15,27), but is consistent with previous publications from this laboratory (21,30,32,34,35). It has been noted that the substrates of the ,8-oxidation enzymes do not easily cross the intact mitochondrial inner membrane, thus this membrane must be disrupted before detecting enzyme activity (34). When mitochondria isolated by centrifugation in sucrose density gradients are added to cuvettes for spectrophotometric enzyme assays, sufficient sucrose is carried along to maintain Having established the occurrence of both mitochondrial and peroxisomal isozymes in 2 to 3 d germinated pea seedlings, a partial purification of the EH isozymes was accomplished by disruption of the organelle-enriched fractions, removal of membranous material by centrifugation, (NH4)2SO4 fractionation, and gel permeation chromatography (Table II).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This result is in marked contrast to reports from other workers on the localization of the $-oxidation enzymes in higher plant cells (6,12,15,27), but is consistent with previous publications from this laboratory (21,30,32,34,35). It has been noted that the substrates of the ,8-oxidation enzymes do not easily cross the intact mitochondrial inner membrane, thus this membrane must be disrupted before detecting enzyme activity (34). When mitochondria isolated by centrifugation in sucrose density gradients are added to cuvettes for spectrophotometric enzyme assays, sufficient sucrose is carried along to maintain Having established the occurrence of both mitochondrial and peroxisomal isozymes in 2 to 3 d germinated pea seedlings, a partial purification of the EH isozymes was accomplished by disruption of the organelle-enriched fractions, removal of membranous material by centrifugation, (NH4)2SO4 fractionation, and gel permeation chromatography (Table II).…”
Section: Resultssupporting
confidence: 89%
“…The activities of the ,-oxidation enzymes were approximately equally distributed in both organellar fractions (Table I). This result is in marked contrast to reports from other workers on the localization of the $-oxidation enzymes in higher plant cells (6,12,15,27), but is consistent with previous publications from this laboratory (21,30,32,34,35). It has been noted that the substrates of the ,8-oxidation enzymes do not easily cross the intact mitochondrial inner membrane, thus this membrane must be disrupted before detecting enzyme activity (34).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Although we do not exclude the possibility that a (3-oxidation activity is also present in the mitochondria (23), it appears likely that the activities observed in the present work are peroxisomal because the assay conditions used (high CoA concentration and absence of carnitine in the overall (3-oxidation assay, high osmotic pressure of the media in all enzyme assays) would not allow the detection of the mitochondrial (-oxidation activities (32). Moreover, the simultaneous increase of catalase, an ancillary enzyme of fl-oxidation that degrades the H202 formed at the oxidase step, and of malate synthase, a glyoxylate cycle enzyme, suggests that glucose starvation is associated with a general increase of peroxisomal activities.…”
Section: Discussionmentioning
confidence: 77%
“…Recent works have reported that the presence of the /3-oxidation system is exclusively localized in peroxisomes from the non-fatty tissues of potato tubers, mung bean hypocotyls, Jerusalem artichoke tubers and algae (Gerhardt 1983, Macey and Stumpf 1983, Stabenau et al 1984, although some authors claim that mitochondria are involved as in mammalian cells (Wood et al 1986).…”
Section: Introductionmentioning
confidence: 99%